A Model for The Distribution of Bankruptcy Assets of a Company Involving Tax Debt and Labor Debt Based on The Principle of Justice - et al., Krista Yitawati (International Journal of Advanced Science and Technology, 2019)
his study aims to find a model for the distribution of bankruptcy of companies involving tax debt and labor debt based on the principle of justice. The research method used is a normative research method by reviewing the laws and regulations and related legal materials. The need to find a fair policy model in terms of the distribution of bankrupt assets between tax debts and labor debt in a company declared bankrupt by the commercial court is so that no more debate takes place first. Where the position between tax debt and labor debt is the same, namely as preferential creditors who have special rights which are equally protected by the repayment law. Especially with the issuance of the Constitutional Court's decision No.67 / PUU-XI / 2013 which places outstanding wages as a bill that must take precedence over all types of creditors including bills of separatist creditors, state rights bills, auction offices and government-formed public bodies. Of course this raises contradictions between laws and regulations, but if analyzed from the principle of justice, the wages of workers and other rights must be prioritized over repayment compared to the repayment of other creditors. But this right must be stated in the upcoming bankruptcy law so that justice and legal certainty can be created for the parties.